Opportunistic Infection in HIV Patients at Tertiary Care Hospital in Rawalpindi - Javed, Mirza Waseem; Nisar, Shazia; Ahmad, Ejaz; Iqbal, Muhammad; Anwar, Muhammad; Abbas, Syed Yasir (Pakistan Armed Forces Medical Journal, 2025)
Objective: To determine the spectrum of opportunistic infection in human immunodeficiency virus patients at tertiary care hospital.Study Design: Cross-sectional study.Place and Duration of Study: Department of Infectious Diseases, Pak Emirates Military Hospital, Rawalpindi, Pakistan from Jan 2024 to Sep 2024.Methodology: The confirmed cases of human immunodeficiency virus infection of both genders between the age of 18-65 years were included. Patients having any infection before the diagnosis of human immunodeficiency virus infection were excluded from the study. Moreover, those who were not willing to participate and unable to comprehend questions were also excluded. All participants willing to participate were interviewed for demographic details and the clinical examination was done afterwards. Laboratory investigations for the suspected opportunistic infections were done.Results: Of these eighty-one (n=81) patients 74(91.36%) were males and 7(8.64%) were females with a median age of 29.00 (44.00-35.00) years. The median HIV RNA PCR value was 33000.00 (1529.00 - 903341.00) IU/ml while median CD4 counts were 213.00 (71.00-381.00) cell/mm3. The most common opportunistic infection was pulmonary tuberculosis 20(24.69%) followed by Cytomegalovirus infection 18(22.22%) and Toxoplasmosis 17(20.99%). Syphilis was seen in 7(8.64%) while Cryptococcal Meningitis was seen in 3(3.70%). The least common infections were hepatitis B and Ebstein Bar virus infection having a frequency of 1(1.23%).Conclusion: Pulmonary tuberculosis, cytomegalovirus infection and toxoplasmosis were the most common infections observed in individuals with human immunodeficiency virus infection.